Using Virtual Reality to Provide Health Care Information to People With Intellectual Disabilities: Acceptability, Usability, and Potential Utility - Hall, Valerie; Conboy-Hill, Suzanne; Taylor, Dave (JMIR Publications, 2011)
BackgroundPeople with intellectual disabilities have poor access to health care, which may be further compromised by a lack of accessible health information. To be effective, health information must be easily understood and remembered. People with intellectual disabilities learn better from multimodal information sources, and virtual reality offers a 3-dimensional (3D) computer-generated environment that can be used for providing information and learning. To date, research into virtual reality experiences for people with intellectual disabilities has been limited to skill-based training and leisure opportunities within the young to mid age ranges. ObjectiveThis study assessed the acceptability, usability, and potential utility of a virtual reality experience as a means of providing health care-related information to people with intellectual disabilities. We designed a prototype multimodal experience based on a hospital scenario and situated on an island in the Second Life 3D virtual world. We wanted to know how people of different ages and with varying levels of cognitive function would participate in the customized virtual environment, what they understood from being there, and what they remembered a week later. MethodsThe study drew on qualitative data. We used a participatory research approach that involved working alongside people with intellectual disabilities and their supporters in a community setting. Cognitive function was assessed, using the Matrix Analogies Test and the British Picture Vocabulary Scale, to describe the sample. Participants, supported by facilitators, were video recorded accessing and engaging with the virtual environment. We assessed recall 1 week later, using a specialized interview technique. Data were downloaded into NVivo 8 and analyzed using the framework analysis technique. ResultsStudy participants were 20 people aged between 20 and 80 years with mild to severe intellectual disabilities. All participants were able to access the environment and voluntarily stayed there for between 23 and 57 minutes. With facilitator support, all participants moved the avatar themselves. Participants engaged with the scenario as if they were actually there, indicating cognitive presence. Some referred back to previous medical experiences, indicating the potential for experiential knowledge to become the foundation of new learning and retention of knowledge. When interviewed, all participants remembered some aspects of the environment. ConclusionsA sample of adults with intellectual disabilities of all ages, and with varying levels of cognitive function, accessed and enjoyed a virtual-world environment that drew on a health care-related scenario, and remembered aspects of it a week later. The small sample size limits generalizability of findings, but the potential shown for experiential learning to aid retention of knowledge on which consent is based appears promising. Successfully delivering health care-related information in a non-National Health Service setting indicates potential for delivery in institutional, community, or home settings, thereby widening access to the information.